PEMAHAMAN REMAJA TENTANG ULANGAN 6:6-8 RELEVANSINYA BAGI PERANAN ORANG TUA TERHADAP ANAK - Enny Irawati (STT BIBLIKA JAKARTA, 2020)
This research is intended to find a relationship between adolescent understanding of Deuteronomy 6: 6-8 with the role of parents in educating children. This research uses quantitative descriptive methods, namely test analysis, validity test and linkert scale calculation. This research was conducted randomly to high school students in Jakarta and students in Jakarta, Salatiga and Yogyakarta. Data collection, researchers used 2 types of questionnaires for the 2 variables studied. Each questionnaire contained 10 question items with 3 scales: True, Doubtful, False. The research was conducted on 6-8 July 2020. The sexes of respondents were male and female. The age of the respondents between 15-24 years. The results showed that adolescents had a very good understanding of 87.5 percent about the role of parents according to Deuteronomy 6:6-8 and parents had a good role of 78.8 percent in educating children.